S104 The culture microbiome in the lungs of patients with COPD. (2nd December 2011) - Einarsson, G G; Comer, D; Tunney, M M; Elborn, J S
Abstract : Introduction and Aims: Previous studies have shown that the lungs of Cystic Fibrosis (CF) and bronchiectasis (BE, not caused by CF) patients are colonised by a range of aerobic and anaerobic bacteria. As bacteria are also implicated in the pathogenesis and progression of chronic obstructive pulmonary disease (COPD), this study aimed to determine the culture microbiome of the COPD airways. Methods: Samples were collected from 13 stable COPD patients during routine bronchoscopy. Bronchial washings were taken at a single location in the right middle lobe by flushing and removing 30 ml of sterile saline. Samples were cultured under strict anaerobic conditions with bacteria detected by plating on both selective and non-selective agar media and quantified by total viable count (TVC). Identification of the cultured bacteria was performed by amplification and subsequent sequencing of the 16sRNA gene. Results: Mean FEV1 was 1.36 (range 0.84–2.26, mean per cent predicted FEV1, 54%), and the mean ratio (FEV1 /FVC) was 51%. Bacteria were detected in 12/13 samples (92%) with bacteria from the genera Streptococcus [12/13 samples, 92%; mean (range) TVC 9.62×10 5 cfu/ml (1.50×10 3 –1.42×10 7 )] and Haemophilus [4/13 samples, 31%; mean (range) 6.40×10 4 cfu/ml (2.20×10 3 –1.60×10 5 )] most frequently detected. Anaerobic bacteria primarily from the genera Prevotella [8/13 samples, 62%; mean (range) TVC 1.12×10 4 cfu/ml (1.30×10 3 –4.20×10 4 )] and Veillonella [5/13 samples, 38%; mean (range) TVC 1.29×10 5 cfu/ml (4.20×10 3 –3.60×10 5 )] were also detected. Pseudomonas and Moraxella were not detected in any samples. Conclusions: Our results show that bacteria from the genera Streptococcus, Haemophilus, Prevotella and Veillonella are frequently present the airways of patients suffering from COPD. Taking account of the dilutional effect of the bronchial wash procedure and extrapolating to allow comparison with sputum data in our laboratory for CF and BE, the relative load of bacteria from the genera Streptococcus, Prevotella and Veillonella is similar in these three airway diseases. The potential role of these bacteria in the progression and pathogenesis of COPD requires further investigation.